Comparative Assessment of Health Benefits of Praziquantel Treatment of Urogenital Schistosomiasis in Preschool and Primary School-Aged Children. (18th August 2016) - Wami, Welcome M.; Nausch, Norman; Midzi, Nicholas; Gwisai, Reggis; Mduluza, Takafira; Woolhouse, Mark E. J.; Mutapi, Francisca
Abstract : Schistosomiasis is a major public health problem in Africa. However, it is only recently that its burden has become recognised as a significant component impacting on the health and development of preschool-aged children. A longitudinal study was conducted in Zimbabwean children to determine the effect of single praziquantel treatment on Schistosoma haematobium -related morbidity markers: microhaematuria, proteinuria, and albuminuria. Changes in these indicators were compared in 1–5 years versus 6–10 years age groups to determine if treatment outcomes differed by age. Praziquantel was efficacious at reducing infection 12 weeks after treatment: cure rate = 94.6% (95% CI: 87.9–97.7%). Infection rates remained lower at 12 months after treatment compared to baseline in both age groups. Among treated children, the odds of morbidity at 12 weeks were significantly lower compared to baseline for proteinuria: odds ratio (OR) = 0.54 (95% CI: 0.31–0.95) and albuminuria: OR = 0.05 (95% CI: 0.02–0.14). Microhaematuria significantly reduced 12 months after treatment, and the effect of treatment did not differ by age group: OR = 0.97 (95% CI: 0.50–1.87). In conclusion, praziquantel treatment has health benefits in preschool-aged children exposed to S. haematobium and its efficacy on infection and morbidity is not age-dependent.